2013
DOI: 10.1002/uog.12304
|View full text |Cite
|
Sign up to set email alerts
|

Pubic arch angle in prolonged second stage of labor: clinical significance

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 19 publications
1
41
0
5
Order By: Relevance
“…Recently the use of ultrasound has been suggested as an accurate and practical tool to measure the SPA width during pregnancy and prior to labor. Some authors have measured the SPA by 2D ultrasound in women with prolonged second stage and reported a higher risk of obstetric intervention in those with a narrower angle [1]. However, in that study the reproducibility of the SPA measurement by 2D ultrasound was not investigated, though this may represent a main limitation of the suggested technique.…”
Section: Introductionmentioning
confidence: 64%
“…Recently the use of ultrasound has been suggested as an accurate and practical tool to measure the SPA width during pregnancy and prior to labor. Some authors have measured the SPA by 2D ultrasound in women with prolonged second stage and reported a higher risk of obstetric intervention in those with a narrower angle [1]. However, in that study the reproducibility of the SPA measurement by 2D ultrasound was not investigated, though this may represent a main limitation of the suggested technique.…”
Section: Introductionmentioning
confidence: 64%
“…Of course, it would be interesting to assess if the width of the SPA may have a clinical impact on the labor outcome and more precisely to evaluate if a smaller SPA is associated with an increased risk of prolonged labor and dystocia, as previously suggested by clinical [14], radiological [5,15,16,17] and sonographic studies [6]. This will be the subject of a forthcoming study from our group with the aim of investigating if the maternal pubic ultrasound may be combined with the sonographic parameters of the fetal head descent to predict the chance of a spontaneous vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, the use of 2-D ultrasound has been proposed in the assessment of the subpubic arch angle in women with prolonged second stage of labor [6]. The authors have demonstrated that a smaller angle may predict the risk of caesarean section in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, two studies have used ultrasound as a means of image acquisition for obstetric pelvimetry: the first was performed by the gynecologist [5] at the Chaim Sheba Medical Center in collaboration with the university's medical school of Tel Aviv in Israle, the other from the gynecologist [6] and other experts, at the Prince of Wales Hospital in collaboration with the Honk Hong University.…”
Section: David Publishingmentioning
confidence: 99%